If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m-5=-6+m
We simplify the equation to the form, which is simple to understand
m-5=-6+m
We move all terms containing m to the left and all other terms to the right.
+1m-1m=-6+5
We simplify left and right side of the equation.
m=-1
0=-1
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 6(x+2)=2(2x+4) | | 3x-16(4-2x)=6 | | 24a+-22=-4(1+6a) | | p=2(89)+2(117) | | -2x-3=x+3+3x | | (x+3)+2(x-7)=3x-11 | | a(10)-8=-24 | | 2y^2+4y-198=0 | | 18-43=4(x-2)-5 | | 9x-(4x-15)=50 | | 2(4r+6)=12r+18 | | 8-9=-12 | | 3z+1=4z-8+28 | | 12(x-9)=-5-7 | | 8=(x+0.5)(x+1) | | x*x+10x=1575 | | 3x-64-32x=6 | | x+50+2x+20=90 | | -6k+7k-9k+8k= | | x+50+2x+20=180 | | 2370=320*144*15*x/35000 | | 49a^4b-14a^3b+21ab=0 | | -2(-3x+8)+5=-21 | | 4x-70=12x+2 | | 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x | | x+2+x+4+x^2-3x+3x-2=39 | | 12c^2-13c-35= | | 10x=9x-25 | | -9-6k+9-(2k)= |